Temporary protective coating as well as preparation method and application thereof
By using temporary protective coatings containing fluorocarbon resins and UV resins, the problems of insufficient hydrofluoro acid resistance and binding strength of the coating in the prior art are solved, and higher preparation quality and pass rate are achieved, ensuring the stability and integrity of the glass edge etching process.
Patent Information
- Application Number
- CN202311113293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The existing temporary protective glue has insufficient hydrofluoric acid resistance, alkaline washing properties and the binding force between the coating and glass, resulting in bubbles or fall off during etching of the glass edge after laser cutting, affecting the quality of the prepared foldable glass.
Temporary protective coatings containing fluorocarbon resin, UV resin, initiator and isocyanate curing agent are used to improve the hydrofluoro acid resistance and alkaline washability of the coating by optimizing component ratio and process treatment, and enhance the binding force with glass.
The stability and integrity of the coating during laser cutting and edge etching are achieved, the preparation quality and passing rate of foldable glass are improved, and the coating does not bubble or fall off during the target time.
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of material preparation, and in particular relates to a temporary protective coating and a preparation method and application thereof. Background Art
[0002] With the development of flexible display technology, the bending radius of foldable glass is required to be smaller and smaller. At present, the production of foldable glass is mainly stacking. The thinned large-size glass is bonded together with adhesive through the rolling process, and then cut by CNC, etched and ground. Finally, the thinned glass of the required size is obtained by slicing. After strengthening, the required foldable glass is obtained. The stacking process has many production processes, and due to the limitation of CNC cutting accuracy, the cutting edge roughness is relatively high. Although there are edge etching and grinding processes, the foldable glass finally prepared has edge accuracy problems. With a bending radius of R = 0.5mm, the dynamic bending is screened for 1,000 times, and the pass rate is about 80-85% (the pass rate without edge grinding is only 50%). With the laser cutting process, after the large-scale thinned glass is sprayed with temporary protective glue and cured, it can be directly cut with a laser, which has higher accuracy, no edge grinding is required, and the process is simpler. The edge shape is intact after cutting, and the coating can be completely cleaned by soaking in 1-3% sodium hydroxide aqueous solution for 3-5 minutes. The pass rate of 1,000 screenings with R = 0.5mm dynamic bending can reach more than 90%.
[0003] However, the main resins of existing conventional temporary protective glues are mainly phenolic resins, water-based acrylic resins, water-based polyurethanes, etc., which use phenolic hydroxyl and carboxyl groups to easily react with sodium hydroxide and fall off. However, after testing, the above-mentioned various resins have poor hydrofluoric acid resistance. When the edge of the small piece of folded glass after laser cutting is etched, the coating will bubble or fall off, resulting in poor etching.
[0004] Therefore, how to improve the hydrofluoric acid resistance and alkaline washing performance of the temporary protective glue and the bonding strength of the formed coating with the coating during edge etching is an urgent problem to be solved. Summary of the invention
[0005] In view of this, one purpose of the present application is to provide a temporary protective coating, containing fluorocarbon resin, UV resin, initiator and curing agent, etc., with good film-forming effect, resistant to hydrofluoric acid and washable with alkali, used in the production of foldable glass, with good bonding strength with glass, smooth coating edge after UTG laser cutting, and no bubbling or falling off during the edge etching process within the target time.
[0006] Another object of the present application is to provide a method for preparing a temporary protective coating.
[0007] Another object of the present application is to provide a coating.
[0008] Another object of the present application is to provide an application of a temporary protective coating.
[0009] To achieve the above-mentioned object, the first embodiment of the present application provides a temporary protective coating, comprising component A and component B;
[0010] The A component includes a fluorocarbon resin, a UV resin, an initiator and a solvent, wherein the fluorocarbon resin contains a hydroxyl group;
[0011] The B component includes a curing agent, and the curing agent is an isocyanate curing agent.
[0012] In some embodiments, in the component A, the mass ratio of the fluorocarbon resin, the UV curable resin, the initiator and the solvent is (20-40): (60-80): (3-20): (200-500).
[0013] In some embodiments, the fluorocarbon resin has a hydroxyl value of 50-150 mgKOH / g.
[0014] In some embodiments, the acid value of the UV resin is 100-300 mgKOH / g.
[0015] In some embodiments, the initiator is a free radical polymerization initiator.
[0016] Preferably, the initiator includes at least one of photoinitiator 184 , photoinitiator TPO, photoinitiator BDK, and photoinitiator 1173 .
[0017] In some embodiments, the solvent includes at least one of an ester solvent, an ether solvent, a ketone solvent, and diacetone alcohol.
[0018] In some embodiments, the curing agent is at least one of HDI trimer, HDI biuret, and IPDI trimer, and the molar ratio of the isocyanate group in the curing agent to the hydroxyl group in the fluorocarbon resin is 1:(1-4).
[0019] To achieve the above object, the second embodiment of the present application proposes a method for preparing a temporary protective coating, comprising:
[0020] dissolving the initiator in the solvent to obtain a mixed solution;
[0021] Adding the fluorocarbon resin and the UV resin into the mixed solution and mixing them evenly to obtain the component A;
[0022] The B component is mixed with the A component to obtain the temporary protective coating.
[0023] In some embodiments, the process of dissolving the initiator in the solvent is performed under a light-protected environment.
[0024] In some embodiments, the B component is mixed with the A component before the temporary protective coating is used.
[0025] To achieve the above-mentioned purpose, the third aspect of the present application proposes a coating, including the temporary protective coating of the embodiment of the present application or the temporary protective coating prepared by the preparation method of the temporary protective coating of the embodiment of the present application.
[0026] To achieve the above-mentioned purpose, the fourth aspect of the present application relates to the application of the temporary protective coating of the embodiment of the present application or the temporary protective coating prepared by the preparation method of the temporary protective coating of the embodiment of the present application in the production of foldable glass, and the application includes:
[0027] Forming coatings containing the temporary protective coating on two opposite surfaces of the glass to obtain glass containing the coatings;
[0028] Laser cutting the coated glass into glasses of multiple target sizes;
[0029] The glass layers of the plurality of target sizes are fixed, and then edge etching, first cleaning, alkali solution soaking, second cleaning, and strengthening treatment are sequentially performed to obtain the foldable glass.
[0030] In some embodiments, the method of forming a coating layer containing the temporary protective coating comprises:
[0031] The temporary protective coating is applied to the glass surface, followed by baking and UV curing treatment.
[0032] In some embodiments, the baking temperature is 60-100°C.
[0033] In some embodiments, the baking time is 10-30 minutes.
[0034] In some embodiments, the curing light intensity of the UV curing process is 200-250 mw / cm 2 .
[0035] In some embodiments, the energy of the UV curing process is 1000-2000 mJ / cm 2 .
[0036] In some embodiments, the edge etching is performed in a hydrofluoric acid solution, and the edge etching time is 5-10 minutes.
[0037] In some embodiments, the alkali solution soaking time is 5-40 minutes.
[0038] In some embodiments, the strengthening treatment method includes: chemical strengthening.
[0039] The temporary protective coating of the embodiment of the present application can at least bring the following beneficial effects:
[0040] It contains fluorocarbon resin, UV resin, initiator and curing agent, etc. It has good film-forming effect, is resistant to hydrofluoric acid and can be washed with alkali. It is used in the production of foldable glass. It has good bonding with glass. The edge of the coating is smooth after UTG laser cutting, and there is no bubbling or falling off during the edge etching process.
[0041] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0043] Figure 1 This is a photo of bubbles appearing after edge etching.
[0044] Figure 2 This is a photo of the coating partially falling off during edge etching.
[0045] Figure 3 Photo of the folded glass that was ultimately prepared due to poor etching caused by insufficient acid resistance of the coating and acid penetration at the edges.
[0046] Figure 4 This is a photo of the folded glass showing a smooth appearance on both sides without any defects after the complete preparation process including coating, laser cutting, hydrofluoric acid etching, etc. DETAILED DESCRIPTION
[0047] The embodiments of the present application are described in detail below. The examples of the embodiments are exemplary and are intended to be used to explain the present application, but should not be understood as limiting the present application.
[0048] Throughout the application, the disclosure of numerical ranges includes all values within the entire range and disclosure of further subdivided ranges, including endpoints and subranges given within those ranges.
[0049] In the application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be produced through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0050] The temporary protective coating of the embodiment of the present application includes component A and component B; component A includes fluorocarbon resin, UV resin, initiator and solvent, and the fluorocarbon resin contains hydroxyl group fluorocarbon resin; component B includes curing agent, and the curing agent is isocyanate curing agent.
[0051] The inventive concept of the temporary protective coating of the embodiment of the present application is as follows: the high acid value UV resin has high polarity and excellent adhesion to glass. At the same time, the carboxyl group in the molecule can also react with sodium hydroxide to greatly improve the hydrophilicity and fall off. However, when the pure UV resin is exposed to the air for curing, the oxygen inhibition phenomenon is more obvious. When the coating is thin, the surface layer is difficult to cure, resulting in poor hydrofluoric acid resistance. The addition of hydroxyl-containing fluorocarbon resin and isocyanate curing agent can improve the hydrofluoric acid resistance because the fluorocarbon resin has good hydrophobicity. At the same time, the degree of cross-linking of the glue is greatly improved after the fluorocarbon resin containing hydroxyl and the isocyanate curing agent are cured. At this time, oxygen is not easy to penetrate, the oxygen inhibition phenomenon is greatly reduced, the coating is better cured, and the hydrofluoric acid resistance is greatly improved.
[0052] It should be noted that in the embodiments of the present application, component A may include only fluorocarbon resin, UV curing resin, initiator and solvent, or may include other first components in addition to fluorocarbon resin, UV curing resin, initiator and solvent. Here, the first other component may be acrylic acid phosphate with the function of improving adhesion, or epoxy acrylate with anti-oxidation and polymerization inhibition function, tertiary amine initiator, etc., or at least one of organic tin and organic bismuth with catalytic function, etc. In some cases, the first other component may also be two or more of the materials with the above-mentioned different functions.
[0053] In the embodiments of the present application, the fluorocarbon resin contains hydroxyl groups and can react with an isocyanate curing agent.
[0054] In some embodiments, in component A, the mass ratio of fluorocarbon resin, UV curable resin, initiator and solvent is (20-40):(60-80):(3-20):(200-500), including but not limited to 20:60:3:200, 40:80:20:500, 20:80:20:500, 40:60:3:200 or 30:70:11.5:350, etc.
[0055] In some embodiments, the hydroxyl value of the fluorocarbon resin is 50-150 mgKOH / g, including but not limited to 50 mgKOH / g, 80 mgKOH / g, 100 mgKOH / g, 130 mgKOH / g or 150 mgKOH / g.
[0056] In some embodiments, the acid value of the UV resin is above 100 mgKOH / g, and more preferably 100-300 mgKOH / g. As a non-limiting example, the acid value of the UV resin includes but is not limited to 120 mgKOH / g, 140 mgKOH / g, 160 mgKOH / g, 180 mgKOH / g, 200 mgKOH / g, 240 mgKOH / g, 260 mgKOH / g or 300 mgKOH / g. The acid value of the UV resin within the above range can meet the hydrofluoric acid resistance requirements and can also be well cleaned; if it is less than 100 mgKOH / g, too few carboxyl groups are reserved, and it is difficult to clean with sodium hydroxide; when it is greater than 300 mgKOH / g, the hydrophilicity is too strong, the water absorption rate is too high, and the hydrofluoric acid resistance is reduced.
[0057] As non-limiting examples, the UV resin includes, but is not limited to, at least one of polyurethane acrylate or polyester acrylate, and the like.
[0058] In some embodiments, the initiator is a free radical polymerization initiator. Preferably, the initiator includes but is not limited to at least one of photoinitiator 184, photoinitiator TPO, photoinitiator BDK, photoinitiator 1173, and the like.
[0059] In some embodiments, the solvent includes but is not limited to at least one of ester solvents, ether solvents, ketone solvents, diacetone alcohol, etc. Among them, the ester solvent includes but is not limited to at least one of ethyl acetate, butyl acetate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, etc. The ether solvent includes but is not limited to at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, etc.
[0060] Preferably, the solvent is a ketone solvent, including but not limited to at least one of butanone, acetone, methyl ethyl ketone, cyclohexanone and the like.
[0061] As non-limiting examples, the curing agent includes but is not limited to at least one of HDI trimer (hexamethylene diisocyanate trimer), HDI biuret (hexamethylene diisocyanate biuret), IPDI trimer (isophorone diisocyanate trimer), etc. Preferably, the curing agent is HDI trimer.
[0062] In some embodiments, the molar ratio of isocyanate groups (NCO) in the curing agent to hydroxyl groups in the fluorocarbon resin is 1: (1-4), including but not limited to 1: 1, 1: 2, 1: 3 or 1: 4, etc. In the embodiments of the present application, the curing agent only increases the crosslinking degree of the fluorocarbon resin to dry the surface, and the resin does not need to be completely cured, otherwise it is not easy to wash off during alkali washing.
[0063] In some embodiments, the mass ratio of component A to component B is (404.2-404.8):(2-10), including but not limited to 404.8:3, 404.2:4.5, 403.6:6, 404.8:8 or 404.8:10, etc.
[0064] The temporary protective coating of the embodiment of the present application can at least bring the following beneficial effects:
[0065] It contains fluorocarbon resin, UV resin, initiator and curing agent, etc. It has good film-forming effect, is resistant to hydrofluoric acid and can be washed with alkali. It is used in the production of foldable glass. It has good bonding with glass. The edge of the coating is smooth after UTG laser cutting, and there is no bubbling or falling off during the edge etching process within the target time.
[0066] The preparation method of the temporary protective coating of the embodiment of the present application comprises the following steps:
[0067] S101, dissolving an initiator in a solvent to obtain a mixed solution.
[0068] In some embodiments, the process of dissolving the initiator in the solvent is performed in a light-proof environment to prevent the initiator from decomposing.
[0069] It should be noted that in step S101, it is necessary to ensure that the initiator is completely dissolved in the solvent.
[0070] S102, adding fluorocarbon resin and UV resin into the mixed solution, mixing evenly, and obtaining component A.
[0071] S103, mixing component B with component A to obtain a temporary protective coating.
[0072] In some embodiments, the timing of mixing component B with component A is before the temporary protective coating is used. The purpose of this is that the fluorocarbon resin in component A starts to react with the curing agent in component B immediately after it is added to component B. If the reaction time is too long, gelation will occur.
[0073] The coating of the embodiment of the present application includes the temporary protective coating of the embodiment of the present application, or the temporary protective coating prepared by the preparation method of the temporary protective coating of the embodiment of the present application.
[0074] It is understandable that the coating of the embodiment of the present application can be any coating that needs to have good acid resistance, alkali washability and good film-forming properties. The temporary protective coating of the embodiment of the present application or the temporary protective coating prepared by the preparation method of the temporary protective coating of the embodiment of the present application is used in the production of foldable glass. The application includes the following steps:
[0075] S1. Forming coatings containing temporary protective coatings on two opposite surfaces of glass to obtain coated glass.
[0076] In some embodiments, the glass in step S1 may be large-size thinned glass.
[0077] In some embodiments, a method for forming a coating layer containing a temporary protective coating comprises: applying the temporary protective coating to a glass surface, followed by sequentially performing baking and UV curing treatments.
[0078] In some embodiments, the baking temperature is 60-100° C., including but not limited to 60° C., 70° C., 80° C., 90° C., or 100° C., etc.
[0079] In some embodiments, the baking time is 10-30 min, including but not limited to 10 min, 15 min, 20 min, 25 min or 30 min, etc.
[0080] In some embodiments, the curing light intensity of the UV curing process is 200-250 mw / cm 2 , including but not limited to 200mw / cm 2 、210mw / cm 2 、220mw / cm 2 、230mw / cm 2 、240mw / cm 2 or 250mw / cm 2 The curing light intensity of UV curing treatment is within the above range, which can achieve good curing; less than 200mw / cm 2 , then oxygen inhibition is more obvious; greater than 250mw / cm 2 , the machine will generate a lot of heat, the service life of the lamp will be short, and the heat dissipation by air cooling alone will be insufficient.
[0081] In some embodiments, the energy of the UV curing process is 1000-2000 mJ / cm 2 , including but not limited to 1000mJ / cm 2 、1200mJ / cm 2 、1500mJ / cm 2 、1700mJ / cm 2 or 2000mJ / cm 2 The energy of UV curing treatment is within the above range, which can be cured well; less than 1000mJ / cm 2 , the curing is incomplete; greater than 2000mJ / cm 2 , it has no practical significance.
[0082] In some embodiments, coating methods include but are not limited to spray coating, spin coating, brush coating, etc.
[0083] It should be noted that in the embodiments of the present application, coatings containing temporary protective coatings are formed on two opposite surfaces of the glass respectively. The coating containing temporary protective coatings can be formed on one side of the glass by the above method first, and then on the other side of the glass by the above method; or the coating containing temporary protective coatings can be formed on both sides of the glass by the above method at the same time.
[0084] In some embodiments, the thickness of the coating on each side of the coated glass is 10-18 μm, including but not limited to 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm.
[0085] S2. Laser cutting the coated glass into glasses of multiple target sizes.
[0086] In some embodiments, the target size includes but is not limited to 6 inches, 8 inches, or 12 inches, etc.
[0087] In some embodiments, the laser cutting method includes but is not limited to carbon dioxide laser cutting, etc.
[0088] S3. Fix multiple glass layers of target sizes, and then perform edge etching, first cleaning, alkaline solution soaking, second cleaning, and strengthening treatment in sequence to obtain foldable glass.
[0089] In some embodiments, the edge etching is performed in a hydrofluoric acid solution, and the edge etching time is 5-15 minutes.
[0090] As a non-limiting example, the hydrofluoric acid solution is a 5-10 wt % hydrofluoric acid solution, such as a 5 wt % hydrofluoric acid solution, a 7 wt % hydrofluoric acid solution, or a 10 wt % hydrofluoric acid solution.
[0091] As non-limiting examples, the edge etching time includes but is not limited to 5 minutes, 7 minutes, 9 minutes, 11 minutes, 13 minutes or 15 minutes, etc. When the edge etching time is within the above range, the edge shaping is good; when it is less than 5 minutes, the edge etching time is insufficient and jagged edges may appear; when it is greater than 15 minutes, the etching may be too deep, the edge is too sharp, and the bendability is reduced.
[0092] In some embodiments, the alkali solution immersion time is 5-40 minutes, including but not limited to 5 minutes, 10 minutes, 20 minutes, 30 minutes or 40 minutes. Under the premise that the coating is resistant to hydrofluoric acid, the coating can be removed from the alkali solution as quickly as possible.
[0093] In some embodiments, the alkaline solution includes but is not limited to at least one of a sodium hydroxide solution, a potassium hydroxide solution, and the like.
[0094] As an optional example, the alkali solution is a 1-3 wt % sodium hydroxide solution.
[0095] In some embodiments, the first cleaning may be performed using tap water to remove residual hydrofluoric acid and the like.
[0096] In some embodiments, the second cleaning may be performed using deionized water or the like.
[0097] In order to ensure the subsequent strengthening process, the alkaline solution immersion treatment must remove all the coatings on the surface of the folded glass. However, due to differences in the acid resistance and carboxyl content of the coating, the time for complete degumming by alkaline immersion is different. In practical applications, the stronger the acid resistance of the coating, the higher the etching yield, the faster the coating is completely removed in the alkaline solution, and the higher the production efficiency. Ultimately, a balance between the two is achieved.
[0098] In some embodiments, the strengthening method includes: chemical strengthening.
[0099] In the embodiment of the present application, a coating process such as spraying is used to coat the large-sized thinned glass, and a coating is obtained after baking and UV curing. The UTG edge can be etched plastically, and after the protection is completed, it can be easily cleaned with alkali.
[0100] The foldable glass obtained in the embodiment of the present application can be widely used in electronic devices, especially display devices of electronic devices.
[0101] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0102] 1. Source of raw materials
[0103] The sources of some raw materials in the embodiments and comparative examples are shown in Table 1.
[0104] Table 1 Sources of some raw materials in Examples and Comparative Examples
[0105]
[0106]
[0107] 2. Examples and Comparative Examples
[0108] In each embodiment and comparative example 1-8, since the solvent content has no effect on the coating performance, the solvent weight ratio DAA: butanone = 1:2 is fixed, and the total weight is 300 parts; the initiator ratio only needs to ensure that the coating is completely cured, and is fixed to 6wt% of the UV resin (where TPO: 184 = 1:1); the leveling agent only affects the appearance of the coating, and the fluorocarbon resin itself has low surface energy, so there is no need to add a leveling agent. At the same time, the leveling agent has no obvious effect on the coating performance, and the ratio is also fixed; the UV curing energy is uniformly 1500mJ / cm 2, light intensity 200mw / cm 2 The baking time is unified as 20min, and the coating thickness is controlled within the range of 13-15μm.
[0109] Example 1
[0110] (Temporary protective coating)
[0111] The temporary protective coating of this embodiment is composed of component A and component B, wherein:
[0112] Component A is composed of the following components in parts by weight: 20 parts of fluorocarbon resin, 80 parts of UV resin, 4.8 parts of initiator, and 300 parts of solvent; the fluorocarbon resin is Changxing Chemical 4262 resin (hydroxyl value is 140 mgKOH / g), and the UV resin is Guangdong Lan Kelu New Materials 8400D resin (acid value is 140-170, solid content is 100%); the initiator is photoinitiator 184 (Aijianmeng 184) and photoinitiator TPO (Aijianmeng TPO), and the weight ratio of photoinitiator 184 to photoinitiator TPO is 1:1 (2.4 parts by weight each); the solvent is diacetone alcohol (DAA) and butanone, and the weight ratio of DAA to butanone is 1:2 (that is, 100 parts by weight of DAA and 200 parts by weight of butanone.
[0113] Component B is Covestro 3390 isocyanate, with a content of 3 parts by weight.
[0114] (Preparation method of temporary protective coating)
[0115] In a light-proof environment, add diacetone alcohol and butanone into a beaker, then add photoinitiator 184 and photoinitiator TPO, add UV resin and fluorocarbon resin after dissolution, and stir evenly to obtain component A; when using, mix component A and component B evenly to obtain the temporary protective coating of this embodiment.
[0116] (Coating formed by temporary protective paint)
[0117] The temporary protective coating of this embodiment is evenly sprayed on one side surface (e.g., the upper surface) of a clean large-sized thinned glass with a spray thickness of 13-15 μm, baked at 80°C for 20 minutes, and then exposed to light with an intensity of 250 mW / cm 2 、Energy 1500mJ / cm 2 After solidification, the large-sized thinned glass is turned over and the above operation is repeated on the other side surface (for example, the lower surface) to obtain a large-sized thinned glass with coatings on both sides. Subsequently, the large-sized thinned glass with coatings on both sides is cut by carbon dioxide laser to obtain small-sized thinned glass (production of foldable glass)
[0118] The above-mentioned small-sized thinned glass stack of this embodiment is set and fixed by a clamp to obtain a stacking block. Then, the stacking block is placed in a 3wt% hydrofluoric acid solution for edge etching. After etching for 10 minutes, the residual hydrofluoric acid is washed off with tap water to obtain a stacking block after edge etching. After that, the edge-etched stacking block is placed in a 2wt% sodium hydroxide solution and soaked for 5 minutes. The coating can be completely removed, and then it is washed with deionized water to obtain an unstrengthened small piece of foldable glass. Finally, the unstrengthened small piece of foldable glass is strengthened (the strengthening method is: chemical strengthening) to obtain the foldable glass of this embodiment.
[0119] Examples 2-16 and Comparative Examples 1-8 are basically the same as Example 1, except that some raw materials and dosages are designed differently, as shown in Table 2. In addition, in Comparative Examples 1-8, the preparation method of the temporary protective coating is: stirring and mixing the components of the temporary protective coating in a light-proof environment.
[0120] Table 2 Partial raw materials and dosage of Examples 1-16 and Comparative Examples 1-8
[0121]
[0122]
[0123] Note: In Table 2, "S" represents an example, for example, S1 represents Example 1; "D" represents a comparative example, for example, D1 represents Comparative Example 1.
[0124] Comparative Example 9
[0125] (Temporary protective coating)
[0126] The temporary protective coating of this comparative example is composed of the following components in parts by weight: 100 parts of phenolic resin, 0.4 parts of leveling agent BYK333, 100 parts of diacetone alcohol (DAA), and 200 parts of butanone; the phenolic resin is 308 resin produced by Henan Zhongfan Dongsheng New Materials Technology Co., Ltd.
[0127] (Preparation method of temporary protective coating)
[0128] After the phenolic resin was dissolved by heating with butanone at 60° C., the leveling agent BYK333 and diacetone alcohol were added and stirred evenly to obtain the temporary protective coating of this comparative example.
[0129] (Coating formed by temporary protective paint)
[0130] The temporary protective coating prepared in this comparative example is directly sprayed on the upper surface of a clean large-sized thinned glass with a spray thickness of 13-15um, and after baking for 20 minutes, it is turned over and sprayed and baked again on the lower surface of the large-sized glass to obtain a large-sized thinned glass with coatings on both sides. Subsequently, the large-sized thinned glass with coatings on both sides is cut by laser to obtain a small-sized thinned glass.
[0131] Comparative Examples 10-16 are basically the same as Comparative Example 9, except that some raw materials and parameter designs are different, see Table 3 for details.
[0132] Table 3 Partial raw materials and parameter design of comparative examples 9-16
[0133]
[0134]
[0135] Note: In Table 3, "D" represents a comparative example, for example, D9 represents comparative example 9.
[0136] 3. Performance Test
[0137] 1. Test methods
[0138] (1) Hydrofluoric acid resistance test
[0139] A small piece of thinned glass according to the embodiment or comparative example is placed in a 3 wt % hydrofluoric acid solution for edge etching, and the surface coating state of the small piece of thinned glass at different times is observed.
[0140] (2) Alkaline washability test
[0141] A small piece of thinned glass in the embodiment or comparative example is immersed in a 2 wt % sodium hydroxide solution, and the surface coating state of the small piece of thinned glass at different times is observed.
[0142] 2. Test results
[0143] The test results of the surface coating properties of the small pieces of thinned glass in the embodiments and comparative examples are shown in Table 4, where OK means that there is no abnormality in the coating.
[0144] Table 4 Surface coating performance test results of small pieces of thinned glass in the examples and comparative examples
[0145]
[0146]
[0147]
[0148] From Table 4 and Figure 1-4It can be seen that the temporary protective coatings of the embodiments of the present application are compared with the temporary protective coatings of the comparative examples. The temporary protective coatings used for the small-piece thinned glass in the preparation process of foldable glass have a coating that is both resistant to hydrofluoric acid and can be washed with alkali.
[0149] Specific:
[0150] Comparative Examples 1-3 and Comparative Example 4 show that as the UV resin content decreases and the fluorocarbon resin content increases, the hydrofluoric acid resistance of the coating gradually increases, but the alkali washing time is prolonged.
[0151] By comparing Examples 1 and 4-7, it can be seen that as the curing agent content increases, the hydrofluoric acid resistance of the coating gradually increases, and the alkali washability slightly decreases, but the coating can be completely removed.
[0152] Comparative Examples 1-3 and Comparative Example 8 show that when the fluorocarbon resin content is too low, the crosslinking degree of the coating is low and the hydrofluoric acid resistance of the coating cannot be guaranteed.
[0153] It can be seen from Examples 1-9 and 10-16 that different combinations of fluorocarbon resins and high acid value resins can satisfy the acid resistance and alkali washability characteristics.
[0154] By comparing Examples 1-7 and 8-9, it can be seen that the type of trimer curing agent has no significant effect on the properties of the coating.
[0155] It can be seen from the comparison of Example 1 and Comparative Examples 9-16 that conventional phenolic resin or polyurethane emulsion, water-based acrylic resin coating can be easily washed off by alkaline washing, but its hydrofluoric acid resistance is poor (less than 15 minutes required for edge etching), and it is not suitable for temporary protection in the preparation process of folding glass.
[0156] It can be seen from Example 1 and Comparative Examples 1-3 that when there is no curing agent or no fluorocarbon resin, the coating cannot meet the hydrofluoric acid resistance property.
[0157] It can be seen from Example 1 and Comparative Example 5 that when the acid value of the UV resin in the coating is too low, the alkali washability property cannot be met.
[0158] It can be seen from Example 1 and Comparative Examples 6-7 that the fluorocarbon resin cannot meet the hydrofluoric acid resistance of the coating after being replaced with ordinary hydroxypropylene resin.
[0159] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0160] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0161] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A temporary protective coating, characterized in that: It includes component A and component B; The component A comprises a fluorocarbon resin, a UV resin, an initiator and a solvent, wherein the fluorocarbon resin is a fluorocarbon resin containing a hydroxyl group; The B component includes a curing agent, and the curing agent is an isocyanate curing agent.
2. The temporary protective coating according to claim 1, characterized in that: In the component A, the mass ratio of the fluorocarbon resin, the UV curable resin, the initiator and the solvent is (20-40): (60-80): (3-20): (200-500).
3. The temporary protective coating according to claim 1, characterized in that: The hydroxyl value of the fluorocarbon resin is 50-150 mgKOH / g; And / or, the acid value of the UV resin is 100-300 mgKOH / g.
4. The temporary protective coating according to claim 1, characterized in that: The initiator is a free radical polymerization initiator; and / or, the solvent comprises at least one of an ester solvent, an ether solvent, a ketone solvent, and diacetone alcohol; And / or, the curing agent is at least one of HDI trimer, HDI biuret, and IPDI trimer, and the molar ratio of isocyanate groups in the curing agent to hydroxyl groups in the fluorocarbon resin is 1:(1-4).
5. The temporary protective coating according to claim 4, characterized in that: The initiator includes at least one of photoinitiator 184 , photoinitiator TPO, photoinitiator BDK, and photoinitiator 1173 .
6. A method for preparing a temporary protective coating as claimed in any one of claims 1 to 5, characterized in that: include: dissolving the initiator in the solvent to obtain a mixed solution; Adding the fluorocarbon resin and the UV resin into the mixed solution and mixing them evenly to obtain the component A; The B component is mixed with the A component to obtain the temporary protective coating.
7. The method according to claim 6, characterized in that The process of dissolving the initiator in the solvent is carried out in a light-proof environment; And / or, the B component is mixed with the A component before the temporary protective coating is used.
8. A coating, characterized in that The temporary protective coating comprises the temporary protective coating as claimed in any one of claims 1 to 5 or the temporary protective coating prepared by the method of claim 6 or 7.
9. Use of the temporary protective coating according to any one of claims 1 to 5 or the temporary protective coating prepared by the method of claim 6 or 7 in the production of foldable glass, characterized in that: The application includes: Forming coatings containing the temporary protective coating on two opposite surfaces of the glass to obtain glass containing the coatings; Laser cutting the coated glass into glasses of multiple target sizes; The glass layers of the plurality of target sizes are fixed, and then edge etching, first cleaning, alkaline solution soaking, second cleaning, and strengthening treatment are sequentially performed to obtain the foldable glass.
10. The use according to claim 9, characterized in that: The method for forming a coating layer containing the temporary protective coating comprises: Applying the temporary protective coating to the glass surface, followed by baking and UV curing treatment; And / or, the edge etching is performed in a hydrofluoric acid solution, and the edge etching time is 5-15 minutes; And / or, the alkali solution soaking time is 5-40min; And / or, the strengthening treatment method includes: chemical strengthening.
11. The use according to claim 10, characterized in that: The baking temperature is 60-100°C; And / or, the baking time is 10-30min; And / or, the curing light intensity of the UV curing treatment is 200-250mw / cm 2 ; And / or, the energy of the UV curing treatment is 1000-2000mJ / cm 2 .
Citation Information
Patent Citations
Alkali-soluble resin and alkali-soluble resin-containing UV cured hydrofluoric acid-resistant protection glue composition
CN104497204A
Preparation method of fluorine-containing alkali-soluble UV resin and resin UV ink composition
CN111004376A
pellicle
JP1997160222A
System For Worker Portfolio Construction Using Text Mining And System For Worker Information Management Using Blockchain
KR1020240069849A
Coating liquid and article using same
US20210087434A1